Global competition of an organization: Managerial analysis of IBM’s global operations under the concepts - value chain, value network and value shop - Kwadade-Cudjoe, Francis (Archives of Business Research, 2021)
Globalization has been one of the strategies many organizations looking to achieve competitive advantage in their markets of operation have been implementing. It has been in existence since the Europeans and Americans started to move into other continents to conquer nations within those continents. Globalization involves the movement of an organization to other parts of the globe in order to utilize the opportunities normally available in those countries for manufacturing of products and trading. There are many strategies through which organizations could use to go global. However the most popular strategies are alliances, acquisitions, mergers and joint ventures. Most organizations which go global usually look for how they could cut cost by utilizing the cheaper natural and human resources available in those countries for production of goods and services. These organizations which go global are called multi-national companies (MNCs), as they usually have assets in the countries they operate from. Some organizations have been able to benefit substantially from globalization, whilst others not. The successful organizations have been able to achieve competitive advantage and some of them have even been able to attain sustained competitive advantage in their fields of operation.